Capacity and mechanisms of plastic deformation in β-Lu2Si2O7. (1st April 2017) - Tian, Zhilin; Zheng, Liya; Wang, Jiemin; Wang, Jingyang
Abstract: RE2 Si2 O7 disilicates are promising candidates for oxidation resistant interfacial phase in SiC fiber-reinforced SiC matrix composites due to their good damage tolerance, good phase stability and compatible thermal expansion coefficients with SiC. We herein investigate the capacity and mechanisms of plastic deformation in β-Lu2 Si2 O7 by a combination of Hertzian indentation experiment and transmission electron microscopy observation. A large amount of (1 1 0) deformation twinning, dislocations and slip bands are observed. For the common twinning mode, fewer atomic shuffle types, small shear strain, and low shear modulus in the twinning direction help explain the prevalence of this mode. Graphical abstract: